Program Pembinaan UMKM Desa Sidodadi: Membangun Kunci Sukses Warga dalam Berwirausaha - Enanto Harun Satrio; UM, Bagas Dwi Ardianto; UM, Dina Shofiana; Karina Aurel Naviezenia; Muhammad Zainur Rifqi; Meyshela Gracia; Wildan Kanzul Fikri; Dika Aurelya Aleandra Taroreh; Reihan Fitroh Aldisar; Abdul Rahman Prasetyo (Nexus Publishing, 2025)
The development of Usaha Mikro, Kecil, dan Menengah (UMKM) is an important step in improving the economic welfare of rural communities, such as in Sidodadi Village, which is rich in local businesses such as chip, tempeh, tofu, and dairy production. This program was designed to address various challenges faced by UMKM, particularly in the areas of marketing, access to technology, and business management. Through training methods involving entrepreneurship experts, the activities provided knowledge about digital marketing strategies and sales techniques, such as closing techniques via WhatsApp and selling on e-commerce platforms. Evaluation results showed an increase in residents’ understanding of digital marketing as well as better collaboration among UMKM actors. Through a participatory approach, residents were actively involved and encouraged to innovate and collaborate in reducing production costs. This program had a positive impact on enhancing the competitiveness of UMKM in Sidodadi Village in broader markets and is expected to serve as a foundation for the sustainability of the village economy.